The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ma12193130
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Oxidation Mechanism of Vermicular Graphite Cast Iron

Abstract: The oxidation mechanism of vermicular graphite cast iron was studied. The oxidation reaction starts from graphites and diffused slowly. Graphites in vermicular graphite are interconnected, coral-like clusters, providing the main oxidation core and channel. The worm-like graphites on the surface are mostly oxidized and form oxide affected zones. The oxide films are composed of a loose oxide layer with the phases of Fe3O4, Fe2O3, and FeO, and a dense passivation layer with FeO and Fe2SiO4. After oxidation, pearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…According to Ref. [12], Fe 2 O 3 is flaky and needle-like, Fe 3 O 4 is blocky, and in the oxidation process, the oxide layer of RuT400 mainly consists of FeO, Fe 2 O 3 , Fe 3 O 4 , and Fe 2 SiO 4 .…”
Section: Morphology Of the Oxide Layermentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ref. [12], Fe 2 O 3 is flaky and needle-like, Fe 3 O 4 is blocky, and in the oxidation process, the oxide layer of RuT400 mainly consists of FeO, Fe 2 O 3 , Fe 3 O 4 , and Fe 2 SiO 4 .…”
Section: Morphology Of the Oxide Layermentioning
confidence: 99%
“…At present, researches on the oxidation of VGI involve many aspects. Guo et al [12] studied the oxidation mechanism of VGI at 530 °C. They observed that the oxidation reaction started from the vermicular graphite and diffused from the outside to the inside.…”
Section: Introductionmentioning
confidence: 99%
“…After the oxidation of graphite, voids or pores are developed that lead to oxygen penetration inside the metal matrix, causing subsurface oxidation. Lin et al [29] and Guo et al [30] demonstrated that flake graphite and vermicular graphite cast irons had worse hightemperature oxidation resistance compared to nodular cast iron due to severe subsurface oxidation. Since graphite flakes were almost interconnected to each other, they served as the primary core and pathway for oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are more suitable for manufacturing large and medium-sized engines. However, the high tensile strength of CGI means that machining requires greater cutting force, high toughness makes it difficult to remove metal and low thermal conductivity leads to difficult heat dissipation and short service life of tools [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%